Analisis Faktor Tingkat Literasi Keuangan Mahasiswa AMIK Depati Parbo Kerinci - R, Ferdinal; Elvina Sandra (Haka Vyza Media, 2024)
This study aims to analyze the level of financial literacy of AMIK Depati Parbo Kerinci students, along with the factors that influence it. This study is quantitative, with a saturated sample consisting of all AMIK Depati Parbo Kerinci students. The data analysis technique used is multiple linear regression. The results of this study indicate that there is a significant influence between gender, parental education level and parental income level on the financial literacy of AMIK Depati Parbo Kerinci students.